Prospective evaluation of pregnancy outcome in an Italian woman with late-onset combined homocystinuria and methylmalonic aciduria - Elvira Grandone; Pasquale Martinelli; Michela Villani; Gennaro Vecchione; Lucia Fischetti; Angelica Leccese; Rosa Santacroce; Gaetano Corso; Maurizio Margaglione (BMC, 2019)
Abstract Background Cobalamin metabolism disorders are rare, inherited diseases which cause megaloblastic anaemia and other clinical manifestations. Early diagnosis of these conditions is essential, in order to allow appropriate treatment as early as possible. Case presentation Here we report the case of a patient who was apparently healthy until the age of 20, when she presented with impaired renal function and normocytic anaemia. At the age of 34, when her first pregnancy resulted in an intrauterine death of a morphologically normal growth-restricted foetus, she was diagnosed with homocystinuria and methylmalonic aciduria due to cyanocobalamin C (cblC) defect, which was confirmed by molecular investigation. Consequently, hydroxocobalamin was administered to correct homocysteine plasma levels. This treatment was efficacious in lowering homocysteine plasma levels and restored anaemia and renal function. During a second pregnancy, the patient was also administered a prophylactic dose of low molecular -weight heparin. The pregnancy concluded with a full-term delivery of a healthy male. Conclusions This case emphasises the importance of awareness and appropriate management of rare metabolic diseases during pregnancy. We suggest that women with late-onset cblC defect can have a positive pregnancy outcome if this metabolic disease is treated adequately.